BIOM-53. DIFFUSION MR IMAGING DERIVED APPARENT DIFFUSION COEFFICIENT AS A POTENTIAL BIOMARKER OF CLINICAL OUTCOME IN RECURRENT CENTRAL NERVOUS SYSTEM LYMPHOMA. (9th November 2020) - Ho, Ka-wai; Nosov, Anton; Young, Robert; Grommes, Christian
Abstract: BACKGROUND: Studies have shown that diffusion-weighted imaging (DWI) derived apparent diffusion coefficient (ADC) measurements inversely correlate with tumor cell density and may have prognostic value in newly-diagnosed CNS lymphoma patients. This study characterizes ADC measurements in a relapsed/refractory CNS lymphoma population and describes the potential prognostic value of ADC measurements in these patients. METHODS: ADC measurements were assessed in immunocompetent patients enrolled on a prospective clinical trial studying ibrutinib-based treatment in recurrent/refractory CNS lymphoma (NCT02315326; 42 treated with single agent ibrutinib and 15 with an ibrutinib containing combination). Measurements were normalized to values contralateral to the lesion to generate an ADC measurement ratio. Imaging and clinical variables were correlated with treatment response. High-quality lesions were defined as areas with clear delineation from preserved brain parenchyma ≥ 10mm in maximal transverse dimension. Cerebral spinal fluid (CSF) was collected at time of MR imaging in all patients. RESULTS: Thirty-nine out of 57 patients had lesions with measurable ADC of which 17 (44%) were high-quality ADC lesions. The median ADCmean ratio was 0.909 (range 0.497–1.444). There was no association between ADC ratios and tumor volume, CSF cell count, or CSF protein. The high-quality lesions had a median ADCmean ratio of 0.774 (range 0.497–1.051). These patients with a high ADCmean ratio (≥ 0.774) had increased rates of partial and complete responses (p=0.057) as well as a longer progression free survival (PFS; median not reached) compared to those with low ADCmean ratios (< 0.774; median PFS=1.5 months, p=0.016). CONCLUSION: ADC ratios in the recurrent CNS population do not correlate with tumor size, cell count, or protein in the CSF. In high-quality DWI measurements, ADC might be a prognostic marker in relapsed/refractory CNS lymphoma patients treated with ibrutinib.